The “urban sprawl” effect on the out-of-town real estate market - Kiakou, Athina (Open Science Journal, 2017)
This paper examines the “urban sprawl” effect on out-of-town real estate market. There are many factors leading to urban sprawl and modulating exurban real estate market. In order to identify these factors, a survey conducted in the Larisa city fringes. Demand, which is a formulation of a number of variables, was determined using two different methods: a) the interview survey which is a descriptive method of identifying the characteristics that affect the property market and b) statistical analysis which is a quantitative assessment of suburban property demand, based on the stochastic method of hedonic regression. According to the questionnaire survey, land value is dependent on adjacency to road infrastructure, distance of the property from the city centre urban land use concentration and physical features of the property which are view adjacent to the road, shape and size of lot. The outcome that land value is dependent on the existence of important economic activity in the property’s locality is consistent with the hedonic regression result, according to which there is a strong and statistically significant correlation between land sale price and distance from a major central use. Hence, the role of theses land uses is documented reflecting the impact of urban sprawl on land market. This correlation is negative, statistical significant and follows a different function for each axis of development. The function depends on type and cycle of development of each area which have a different distribution and type of land uses. That is to say, each function expresses the different way that emerging land uses and urban morphology affect the land market. This outcome is important because allows us to assess the effect of a future spatial planning project of activities in the tertiary sector, on out-of-town real estate market.